Experimental studies of heat exchanger based on heat tubes - Серко, Микола Васильович; Мариненко, Володимир Іванович; Рогачов, Валерій Андрійович; Хайрнасов, Сергій Монісович (Technology audit and production reserves, 2014)
The currently applied methods of a deep heat recovery in boiler units use recuperative, regenerating, mixing and combined heat exchangers. The progress analysis of developments in the field of recovery facilities shows that their main disadvantages include high weightsize parameters, low aerodynamic heating characteristics and, as a consequence, high metal input, capital and operating costs. For reducing weight-size parameters, a heat recovery exchanger based on heat tubes was designed. The heat exchanger peculiarities is geometrical characteristics of the used heat tubes, in particular, inner longitudinal finning, serving as a capillary structure and a small outside diameter of tubes. As a result of the studies, it was found that the heat transfer surface of the heat exchanger based heat tubes is on the average 4…5 times less than the surface area of a conventional recuperative heat exchanger, under the same heat power. The obtained experimental data are useful and important for further studies of heat exchangers based on small-diameter heat tubes with inner longitudinal finning. Their implementation will increase thermal aerodynamic, weight-size and performance criteria of the heat exchange facility under the development in various industries.